Interprofessional Collaboration Penanganan Awal Kasus Preeklamsia Dan Eklamsia Di Kabupaten Wajo Sulawesi Selatan - Karsa, Nevi Sulvita; Andi Mappaware, Nasrudin; Mokhtar, Shulhana; Alamanda Irwan, Andi; Mursyid, Muhammad; Makmun, Armanto; Adriansyah, Aan; Irsan, Muhammad; Parningan, Zherant (Window of Community Dedication Journal, 2021)
Preeclampsia and eclamsia are a unity of the disease. The term unity of the disease means that both events are essentially the same because of eclamsia which is an increase of the heavier and more dangerous pre-eclampsia with the addition of certain symptoms. Interprofessional collaboration (IPC) is a strategy in improving the quality of service. The IPC strategy aims to improve patient safety, improve human resources quality, and transform health care systems more effectively. Thus IPC is important in hospital services. Health workers, namely doctors, midwives, nurses and pharmacists to be able to solve the problem of obstetric emergency can be done training and applying interprofessional collaboration (IPC) in providing education, screening and initial management by doctors, midwives, nurses and pharmacists in lowering unwanted events or death in cases of preeclampsia and eclamsia. Training is given to health workers, especially doctors, midwives, nurses and pharmacists in conducting IPC practice divided into 4 dimensions, namely Assessment of Interprofessional Team Collaboration Scale (AITCS) including partnerships, Cooperation, Coordination, Shared Decision Making. Keywords: Interprofessional collaboration, preeclampsia, eclamsia